Study on survivability of 18650 Lithium-ion cells at cryogenic temperatures. (June 2018) - Nandini, K.; Usha, K.; Srinivasan, M.S.; Pramod, M.; Satyanarayana, P.; Sankaran, M.
Highlights: The present work highlights the passive survivability of Commercially-Off-the-Shelf (COTS) 18650 lithium-ion cells, at extreme low temperatures below −150 °C in a thermal environment similar to lunar night rover mission scenario. The work employs a comprehensive approach of monitoring cell terminal voltage in-situ during the thermal soak and adjudging the overall health of the cells by conducting some complementary tests both prior-to and after thermal soak like, visual examinations, dimensional measurements, Residual Gas Analysis, electrical tests and 3Dimentional x-ray Computed Tomography analysis. To make the understanding more comprehensive, the test is extended to include cells from different manufacturers with different nameplate capacities and each at two different State Of Charge. Abstract: Passive survivability of Commercially-off-the-shelf 18650 lithium-ion cells is tested in a thermal scenario similar to lunar night. Survivability of cells in particular and battery pack in general is crucial for resumption of function of any lunar exploration rover after hibernation at every lunar night. The test is designed to include a batch of Commercial lithium-ion cells from different manufacturers, with different nameplate capacities and different States of Charge. The cell behaviour during the test is monitored in-situ using cell terminal voltage measurements. To comprehend the effect of exposure to extreme low temperatures some complementary tests like visual examination, dimensional measurements, Residual Gas Analysis to detect any leakage, electrical tests to appraise electrical performance and 3 dimensional x-ray computed tomography analysis to view cell internal features are carried out at ambient conditions on cells both prior-to and after soaking at low temperatures. Results indicate successful survivability of tested cells after extreme thermal soak without any significant physical or internal damage or electrical performance degradation. Variation in cell terminal voltage with temperature is a reversible change attributed to the reversible phenomenon of freezing of cell electrolyte which furthermore is confirmed through ex-situ measurement of freezing point of electrolyte extracted from tested cells.